2007
DOI: 10.4049/jimmunol.178.9.5991
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Human Complement Factor H Sensitizes Non-Small Cell Lung Cancer Cells to Complement Attack and Reduces In Vivo Tumor Growth

Abstract: Malignant cells are often resistant to complement activation through the enhanced expression of complement inhibitors. In this work, we examined the protective role of factor H, CD46, CD55, and CD59 in two non-small cell lung cancer cell lines, H1264 and A549, upon activation of the classical pathway of complement. Complement was activated with polyclonal Abs raised against each cell line. After blocking factor H activity with a neutralizing Ab, C3 deposition and C5a release were more efficient. Besides, a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 34 publications
2
87
0
Order By: Relevance
“…As a loading control, samples were stained for β-actin. 35 While fH has been described as contributing to the protection of several solid tumors and tumor cell lines, [19][20][21][36][37][38][39] its involvement in the resistance of CLL cells to CDC has not yet been reported. By contrast, the role of CD55 and CD59 in the context of CLL has been investigated in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…As a loading control, samples were stained for β-actin. 35 While fH has been described as contributing to the protection of several solid tumors and tumor cell lines, [19][20][21][36][37][38][39] its involvement in the resistance of CLL cells to CDC has not yet been reported. By contrast, the role of CD55 and CD59 in the context of CLL has been investigated in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that complement factor H is expressed and secreted by many non-small cell lung cancer (NSCLC) tumors (17). Factor H is an inhibitor of complement activation and promotes tumor growth in vivo (18). The aim of the present study is to explore whether factor H levels are detectable in bronchial fluids of lung cancer patients and to evaluate its potential diagnostic usefulness.…”
Section: Introductionmentioning
confidence: 99%
“…14 -17). For example, down-regulation of CD59 and complement system factor H allows sensitization of non-small cell lung carcinoma (NSCLC) cells and their elimination via the complement system (18). Further support for this idea comes from studies demonstrating that expression of CD59 and CD55 on NSCLC cells was highly correlated with the histology and prognosis of the disease (9,11).…”
mentioning
confidence: 58%